Effect of cutting length, diameter and treatment with Indole butyric acid (IBA) in rooting woody cuttings of Hayward kiwi variety - تنزكلي, رنيم; جرجس مخول , (Latakia University Journal -Biological Sciences Series, 2023)
This study was conducted during the years 2020-2021 on woody cuttings of kiwi cultivar "Hayward" in an olive propagation nursery in Lattakia governorate. To determine the possibility of rooting using woody cuttings with diameters (4-6 mm) and (8-10 mm), and treated with three concentrations of indole butyric acid (IBA) (3000-4000-6000 ppm), with testing two depths of immersion of the bases of the cuttings in the hormonal solution 3 And 6 cm, and dipping times of 10 and 15 seconds. The results of the study showed that the treatment of lignified cuttings with IBA at a concentration of ppm4000 gave the best results with a callus percentage of 81.66%. the rooting rate reached 73.33% compared to the two concentrations (3000-6000) ppm. The results of the study also showed the superiority of the treatment with a dipping depth of 3 cm over the rest of the treatments with a callus percentage of 85.55% and a rooting rate of 80%, with a callus rate of 76.66% and a rooting rate of 70%. So excel Duration 10 seconds on the rest of the studied transactions. The results of the effect of the interaction between the three factors (hormone concentration, depth of immersion, duration of immersion) in rooting kiwi cuttings showed that treatment (T5) with a concentration of 4000 ppm, a depth of immersion of 3 cm, and a duration of 10 seconds was superior to the rest of the treatments; it gave a callus percentage of 100% and a rooting rate of 93.33%